Peningkatan Kompetensi Wirausaha Literasi Mahasiswa Melalui Penerapan Edu-technopreneurship (Improving Literacy Entrepreneurial Student Competence through implementing Edu-Technopreneurship) - Chafit Ulya (Indonesian Language Education and Literature, 2023)
This study aims to explain the procedures for implementing edu-technopreneurship in improving student literacy entrepreneurial competence. The research used classroom action research. The research participants were 40 students and one collaborator lecturer. Data collection techniques were taken from journals, questionnaires, observations, interviews, and document analysis. Test the validity of the data using data source triangulation, method triangulation, and informant review, as well as self-validation, peer validation, and academic validation. The data analysis technique used an interactive analysis model. The results of this study indicated that the procedure for implementing edu-technopreneurship consists of four stages, namely planning, implementation, evaluation, and competition. The application of edu-technopreneurship is proven to improve students' entrepreneurial literacy competence in three dimensions, namely knowledge, skills, and entrepreneurial attitude.Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan prosedur penerapan edu-technopreneurship dalam meningkatkan kompetensi wirausaha literasi mahasiswa. Jenis penelitian ini adalah penelitian tindakan kelas. Partisipan penelitian adalah 40 mahasiswa dan satu dosen kolaborator. Teknik pengumpulan data menggunakan jurnal, kuesioner, observasi, wawancara, dan analisis dokumen. Uji keabsahan data menggunakan triangulasi sumber data, triangulasi metode, dan review informan, serta validasi diri sendiri, validasi rekan sejawat, dan validasi akademik. Teknik analisis data menggunakan model analisis interaktif. Hasil penelitian ini menunjukkan bahwa prosedur penerapan edu-technopreneurship terdiri atas empat tahapan, yaitu perencanaan, implementasi, evaluasi, dan kompetisi. Penerapan edu-technopreneurship terbukti mampu meningkatkan kompetensi wirausaha literasi mahasiswa pada tiga dimensi, yaitu pengetahuan, keterampilan, dan sikap berwirausaha.